Microscopic Dimensions Engineering: Stepwise Manipulation of the Surface Wettability on 3D Substrates for Oil/Water Separation. Issue 5 (30th November 2015) - Du, Ran; Gao, Xin; Feng, Qingliang; Zhao, Qiuchen; Li, Pan; Deng, Shibin; Shi, Liurong; Zhang, Jin
Abstract : Microscopic dimensions engineering is proposed to devise a series of 3D superhydrophobic substrates with microstructures of different dimensions. Combined theoretical modeling and experiments give the relationship of surface roughness and superhydrophobic properties, important for guiding the design of superior superwettable materials for water remediation and other uses.